Pengaruh Presepsi Harga Dan Restoran Atmosphere Terhadap Keputusan Pembelian Konsumen Pada Restoran 360 Warung Makan - Missil Indrawati; Youmil Abrian (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was motivated by several problems, the fluctuating number of visits to the 360 ​​food stalls, the many consumer complaints about the restaurant but it was still crowded with visitors, inadequate lighting inside the restaurant, and inadequate parking. The research purpose is to examine how restaurant ambiance and price perceptions affect consumer choices. This study used a descriptive research design utilizing quantitative data. This study employed both primary and secondary data sources. The participants in this study are guests of the 360 Warung Makan Restaurant. 110 customers made up the research sample, which was selected using a non-probability sampling technique. A Likert scale questionnaire that had undergone validity and reliability testing was used as the data-gathering tool. SPSS 25.00 was used to process the research's data. The research results show that price perception is in the sufficient category, namely 3.07%, then restaurant atmosphere is in the 3.02% category and purchasing decisions are in the 3.06% category. The price perception value (X1) has a Beta or Standardized Coefficient of 0.501 with T count (6.468) with a significance of 0.000 <0.05, thus the restaurant atmosphere variable (X1) has a positive and significant effect on purchasing decisions (Y), hence the hypothesis in restaurant atmosphere research (X2) has a Beta or Standardized Coefficient of 0.352 with T count (4.542) with a significance of 0.000 <0.05, thus the restaurant atmosphere variable (X2) has a positive and significant effect on purchasing decisions (Y).